Konstrukcionistično razumevanje identitete v neoavantgardizmu - Vaupotič, Aleš (Amfiteater (Ljubljana), 2025)
The paper addresses the connections between the avant-garde, the neo-avant-garde and new media art through a literary-historical and art-historical approach. It also discusses the technical media of film, video and new media. The authors compare the functioning of a computing machine, as theoretically conceived by Turing, with the creative processes of an avant-garde artist. The authors are particularly interested in the construction and integrity of personal identity in the infosphere, as explored by Luciano Floridi’s philosophy and ethics of information. They then test theoretical insights regarding avant-garde and neo-avant-garde practices by interpreting the neo-avant-garde art projects of Nuša Dragan and Srečo Dragan from the late 1960s and 1970s and trace the continuity of concepts and processes in Srečo Dragan’s new media practice in the 1990s up to the present day. Using the example of artists from Slovenia – a seemingly peripheral but powerful centre of development in both fields – the paper shows how the neo-avant-garde and new media are connected at the level of theory and in the artworks.
Keywords: Ana Nuša Dragan; neoavantgarda; neo-avant-garde; new media art; novomedijska umetnost; osebna identiteta; personal identity; Srečo Dragan; video